A correlogram method to examine the crosstalk of sCMOS sensors. (9th March 2021) - Ling, Z.; Wang, W.; Jia, Z.; Zhou, Q.; Wang, X.; Zhang, C.; Yuan, W.; Zhang, S.N.
Abstract: In recent years, scientific CMOS (sCMOS) sensors have been widely used for imaging and spectroscopy in the optical and soft X-ray bands. A sCMOS camera has been developed, along with its auxiliary algorithms, for soft X-ray imaging spectroscopy, which is equipped with a Gsense400BSI chip operating at a frame rate up to 48 Hz. In this paper, we report the finding of a new crosstalk phenomenon in X-ray imaging data taken with the sCMOS sensor exposed to an Fe55 X-ray source. A simple correlogram method for the diagnostics of the crosstalk is introduced. Experiments are carried out for various set-ups and operating conditions of the sCMOS sensor. It is found that the crosstalk occurs in about 2.0% of the X-ray events registered, and there is no dependence of the crosstalk on the voltage configurations, temperature or entrance window of the chip. The cause of the crosstalk has been identified to be an imperfect isolation of the readout nodes inherent in the design. It is demoustrated that the true X-ray spectrum can be restored after careful correction for this effect, which should be taken into account for applications of accurate X-ray spectroscopy using the Gsense400BSI sCMOS sensor.